2019
DOI: 10.9734/cjast/2019/v35i230175
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Heat Treated Daniella oliveri (Africa Balsam Tree) Wood

Abstract: Aims: This work investigated the effect of thermal modification on some of the physical properties and mechanical properties of Daniella oliveri wood. Study Design: The study design used for this experiment was 3 x4 Factorial experiment in Completely Randomized Design. Place and Duration of Study: The study was conducted at the Federal University of Technology, Akure wood laboratory and the study lasted for 6 months. Methodology: Wood samples were thermally treated at the temperature of 120, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…After determining the density and mechanical parameters of all samples, they were divided into 4 groups (of similar mean values), for modification under different temperature variants. Modification was carried out in 4 temperature variants: 140, 160, 180 and 200 • C. These are the temperatures used when modifying wood for testing [14,21], and in industry [15]. By using several variants of the modification temperature, it was possible to determine how the temperature affects the properties of the wood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After determining the density and mechanical parameters of all samples, they were divided into 4 groups (of similar mean values), for modification under different temperature variants. Modification was carried out in 4 temperature variants: 140, 160, 180 and 200 • C. These are the temperatures used when modifying wood for testing [14,21], and in industry [15]. By using several variants of the modification temperature, it was possible to determine how the temperature affects the properties of the wood.…”
Section: Methodsmentioning
confidence: 99%
“…Absorption occurs when the oil temperature drops after the modification with samples still in the medium, or when the material is extracted from the oil immediately after the modification time. Studies have also shown changes of resonance parameters of wood after biological modification [20] and descriptions of changes in the mechanical parameters of wood after thermal modification in a superheated steam atmosphere [8,14,[21][22][23][24]. However, to date, we have found no study describing the direct impact of OHT modification on the acoustic parameters of resonant wood.…”
Section: Introductionmentioning
confidence: 98%
“…The study revealed a three-time shoot density height (7250 ± 454 shoots ha −1 ) and rapid growth following clearance after 34 months compared to ones on weedy plots (2425 ± 215 shoots ha −1 ) suggesting regular cutting of the plant's branches (for use by local people for firewood purposes) could hasten the growth of the plant. Other available physiological findings on the plant are on determination of physicomechanical properties of the plant (wood) when heated at varying degrees of temperature [ 110 ], examination of anatomy and morphology of the root (a measure of proper identification) [ 111 ] and assessment of the plants' biomass [ 112 ].…”
Section: Results (Pharmacological and Safety Properties)mentioning
confidence: 99%